Education, policy, and power: a case study on physiotherapists' opposition to athletic training curriculum. - Lev, Assaf; Been, Ella (Israel Affairs, 2026)
In 2018, Israel's first Athletic Training (AT) department – a health profession specialising in injury prevention and rehabilitation – faced strong opposition from the Physiotherapy (PT) community. This study explores how PTs sought to block the Bachelor of Science (B.Sc.) programme and discredit AT as a profession. Guided by Foucault's power-knowledge framework, we applied Foucauldian Discourse Analysis (FDA) to a four-year dataset, including online posts, union appeals, and legal documents. Findings reveal how Israeli PTs used digital and legal tactics to protect professional boundaries and authority. These efforts reflect broader struggles over legitimacy, occupational power, and control of educational and therapeutic discourse.